Kuchiguse in the Nintendo Switch Console Game - Study of Onomatopoeic in â€œAtsumare: Doubutsu no Moriâ€ - Resha, Firdhani; Firmansyah, Dian Bayu; Kurniawan, Eko (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
This research aims to describe and classify Japanese onomatopoeia, which appear in the form of kuchiguse from animal characters in the Atsumare: Doubutsu no Mori console game. The method used is a qualitative descriptive research method with data collection techniques is the observation note technique. Based on the results of this research, it can be concluded that the onomatopoeic kuchiguse that appears the most is based on characters onomatopoeic found 62 kuchiguse originating from onomatopoeia followed by giyougo, gijougo, giseigo, giongo, and gitaigo. Each animal pronounces onomatopoeia like Sacchi pronouncing giseigo onomatopoeia, Meruborun pronouncing giongo onomatopoeia, and Andesu pronouncing gitaigo onomatopoeia. The spoken kuchiguse can be derived from onomatopoeia and the spoken onomatopoeia by the animal characters has no meaning to the sentence previously spoken. The use of onomatopoeia of kuchiguse as vocabulary in Atsumare: Doubutsu no Mori is another variation of idiolect.